POTENCIAL DE PREDAÇÃO DE Neoseiulus californicus MCGREGOR (ACARI: PHYTOSEIIDAE) SOBRE Tenuipalpus heveae BAKER (ACARI: TENUIPALPIDAE) EM SERINGUEIRA - SILVA, Eliamara Marques; TOSCANO, Luciana Cláudia; COSTA, Geany Giovana Silva (ANAIS DO ENIC, 2017)
-